Autonomia partidária e controle: compliance financeiro partidário - Diogo Fernandes Gradim (2022)
This dissertation aims to propose the creation of a partisan financial compliance program in Brazilian law, delimiting the duties that can be created and the effects that the implementation of the compliance program can generate in sanctioning electoral law. For this, three concepts were analyzed that served as the basis for the compliance proposal. The first is the party autonomy provided by Constitution, which guarantees freedom from interference in the main activity, but admits limitations such as the obligation to render accounts. The second is the constitutional principle of control as a guarantee element of the Constitution, which has limiting and promoting dimensions and seeks to conform public and private agents that are the object of public interest through democratically legitimate means of control. The third is compliance, a form of enforced self-regulation whose application in criminal law and in the prevention of money laundering has extensive knowledge and accumulated experiences, especially international recommendations and internal regulations. Based on these three ideas, it was proposed the guide lines of financial compliance of the parties by law, with regulation by norms provided by TSE, receipt of communication of suspicious operations by the Electoral Justice Intelligence Nucleus. The implementation of the program, meeting the minimum requirements, excludes electoral responsibility and banning processes for facts that directly or indirectly involve party finances and will allow the individual accountability of people who fail to comply with surveillance duties.